Muhammad Quthub's Thought and Its Relevance to Contemporary Islamic Education - Lidinilah , Izul Haq; Siregar, Maragustam (Abdurrauf Journal of Islamic Studies, 2024)
The abstract should be clear, concise, and descriptive. This Muhammad Quthub is an educational figure in the Islamic world, through his ideas and views he has made a major contribution to the science of Islamic education. He said that education is an effort to make a complete human being, namely education that is able to combine mind and heart, spiritual and physical.  This article then wants to explain in more depth the views of Muhammad Qutub and their relevance to contemporary Islamic education today. It will be interesting to see whether Islamic education today is in line with his thoughts or whether it really needs to be evaluated. Furthermore, this research uses a qualitative type of library research, namely by taking sources from published books and journals.  The results of this research show that Islamic education is currently relevant to Muhammad Quthub's views, including the meaning of education, educational goals, educators and educational curriculum [Muhammad Quthub merupakan tokoh pendidikan dunia Islam, lewat gagasan dan pandangannya memberikan kontribsi besar dalam keilmuan pendidikan Islam, ia mengatakan bahwa pendidikan adalah upaya untuk menjadikan manusia seutuhnya, yaitu pendidikan yang mampu memadukan antara akal dan hati, rohani dan jasmani.  Tulisan ini kemudian ingin menjelaskan lebih dalam tentang pandangan-pandangan Muhammad Qutub dan relevansinya terhadap pendidikan Islam Kontemporer saat ini, akan menjadi menarik ketika apakah pendidikan Islam dewasa ini sejalan dengan pemikirannya atau memang perlu dievaluasi. Selanjutnya, penelitian ini menggunakan jenis kualitatif yang bersifat kepustakaan (library research) yaitu dengan mengambil sumber-sumber buku maupun jurnal yang sudah terbit. Analisis Data yang digunakan adalah adalah analisis isi (content analysis) yaitu penelitian yang bersifat pembahasan mendalam terhadap isi suatu informasi tertulis. Adapun hasil penelitian ini bahwa pendidikan Islam sekarang ini relavan dengan pandangan Muhammad Quthub diantaranya makna Pendidikan, tujuan pendidikan, Pendidik, dan  Kuikulum Pendidikan]